KEPATUHAN MINUM TABLET BESI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MENGWI I KABUPATEN BADUNG - Ni Wayan Kertiasih; Luh Seri Ani (E-Jurnal Medika Udayana, 2015)
IRON SUPPLEMENTATION  COMPLIANCE AMONG PREGNANT WOMEN IN HEALTH CENTER MENGWI I DISTRICT BADUNGAnemia in pregnancy give impact to pregnant women and her baby. Pregnant women with anemia can increasing risk of abortus, preterm labor and postpartum hemorrhage. Whereas for baby can causes  stunted growth in their early pregnancy and low birth weight. Iron supplementation tablets (90 tablets) during pregnancy is one of efforts to decreases anemia in pregnancy. Achievement of such supplementation in pregnant women in 2013 in Public Health Center Mengwi I was 73.01%, still below the government's target in 2010 was equal to 90%. The aimed of this study was to determine the compliance of pregnant women consumed iron tablets. Descriptive cross sectional study was done on 30 pregnant women which was selected through convenience sampling through purposive that associated with incidence low birth weight in Gulingan and Kekeran village. Data was gathered through interview. The compliance of pregnant women to consume iron tablet was 30%. The reason of waywardness was caused by forgetfullness (71%), side effects (19%) and discontinuity due to did not control again (10%). The compliance of pregnant women in this study was very low. Thus caused by forgetfulness, side effects and did not control again.